2006
DOI: 10.1007/s10745-006-9036-y
|View full text |Cite
|
Sign up to set email alerts
|

Managing Variability: Herding Strategies in Communal Rangelands of Semiarid Namaqualand, South Africa

Abstract: Herd mobility is a tool for managing environmental variability in African pastoral systems. This study examines the monthly mobility patterns of 24 herds over six years in the 20,000 ha communal area of Paulshoek, Namaqualand, and assesses the social, economic, and ecological factors affecting the livestock movement of individual herds and all herds combined. When the mobility pattern of all herds was considered, no seasonal or between-year differences in response to rainfall were evident. An analysis of indiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 32 publications
2
30
0
Order By: Relevance
“…This may be explained by the influence of nonenvironmental factors, in particular the economic and social circumstances in their temporal environment, on the mobility strategies of 'outside herders' as suggested by Baker and Hoffman (2006) and Turner et al (2011). Although Battistini (1966) emphasized the equal rights of coastal herders on plateau pastures dating back to ancient agreements between the respective clans and families, transhumant herds were still only temporary visitors and therefore might, to a certain extent, have had less access to the grazing grounds around their temporal homesteads than the residential herds.…”
Section: Spatial and Seasonal Differences In Movement Patternsmentioning
confidence: 99%
See 1 more Smart Citation
“…This may be explained by the influence of nonenvironmental factors, in particular the economic and social circumstances in their temporal environment, on the mobility strategies of 'outside herders' as suggested by Baker and Hoffman (2006) and Turner et al (2011). Although Battistini (1966) emphasized the equal rights of coastal herders on plateau pastures dating back to ancient agreements between the respective clans and families, transhumant herds were still only temporary visitors and therefore might, to a certain extent, have had less access to the grazing grounds around their temporal homesteads than the residential herds.…”
Section: Spatial and Seasonal Differences In Movement Patternsmentioning
confidence: 99%
“…Yet, such studies are still rare and most authors using GPS/GIS tools in livestock studies content themselves with more general statements about distances or mobility patterns (e.g. Akasbi et al 2012;Baker and Hoffman 2006;Ouédraogo-Koné et al 2006).…”
Section: Spatio-temporal Variations In Land Usementioning
confidence: 99%
“…Several authors have stressed the importance of socio-economic factors over ecological considerations in determining herding decisions within contemporary pastoral communities (cf. Baker andHoffman 2006, Turner 1999). Socio-economic changes associated with a gradual shift towards wage-dependency and regional economic development reduced labour availability at the cattleposts, which in turn has led to a reduction in seasonal herd mobility.…”
Section: Conclusion: Wider Significance For Pastoral Systems In Africamentioning
confidence: 99%
“…Recognition of the importance of herd mobility in determining environmental sustainability in non-equilibrium pastoral drylands has prompted researchers to understand drivers determining its contemporary use (Baker and Hoffman 2006,Coppolillo 2000,Adriansen and Nielsen 2002,Turner and Hiernaux 2002 and the ecological consequences of its decline (Reid et al 2003,Boone andHobbs 2003). Many of these studies have reported the growing importance of socio-economic rather than environmental factors in determining herding decisions at a microscale by influencing the availability of herding labour, quality of herd management and daily herd itineraries (cf.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation